Art Attack! Tanya Wilson's creative mission to engage children on social issues - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
Meet Tanya Wilson, 41, co-founder of EYEYAH!, an interactive platform that uses visually arresting design and artworks to educate children on important social issues like internet safety, healthy eating, mental health, climate change and so on. The mother of two primary-school-aged daughters is no stranger to the creative industry, having spent two decades developing content and experiences for the likes of Netflix, Facebook, Nike, Coca-Cola, Tiger Beer and Heineken. These days, Tanya and her co-founder Steve Lawler are busy equipping young learners with creative thinking skills which, they believe, are essential to solving the world's complex challenges. ISHAN SINGH finds out more.